Changes in nesting sites abundance and their use by woodpeckers along an urban gradient: a ten-year comparison - Protti Sánchez, Francesca (2019)
Woodpeckers nesting substrate abundance may be reduced by urban expansion, negatively affecting their reproduction. Long-term studies in the tropics are rare but valuable to estimate how urban development has affected ecological communities. We present a ten-year comparison on nesting substrate abundance and their use by Melanerpes rubricapillus and M. chrysauchen woodpeckers along an urban gradient in Golfito, Costa Rica; which include three habitats and three substrates (snags, palms, and posts). Conditions remained unchanged in non-urban areas. In semi-urban areas, snag, posts, and nests on them, have decreased. In urban areas, despite snags and posts remaining constant, their use also decreased. In semi-urban and urban areas, palms and palm nests increased. This long term comparison indicates that woodpeckers took advantage of the increased presence of ornamental palms in gardens.